Desain dan Fabrikasi Mesin Potong Plastik dengan Sistem Pneumatic Berkapasitas 6 Roll - Wega Tama Setya; Mohamad Hakam; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The development of science and technology from time to time has an impact on the industrial sector. Many industries use manufacturing technology in their production processes. PT. Palma Eiko Pack is a plastic forming and custom forming packaging production company and can serve orders in large quantities. In the production process, especially in the process of cutting plastic rolls into certain sizes, it is still done manually so it takes a long time. One plastic roll with a length of 50 m and a width of 1.4 m requires 3 people for the plastic cutting process and in 1 day is able to cut 5 plastic rolls, while the company targets at least 1 day to be able to cut 15 plastic rolls. From these problems, there is a solution to make a machine that is able to work safely, quickly, and does not require a large amount of power with a compressor or air pump as the main driver. The machine is designed simply so that workers can operate the machine easily. The material of the machine also uses materials that are easy to find. Making a machine design concept using the Ulrich method, the first step is to identify theproblem and formulate the problem to choose the concept used. After analyzing the engine frame. Furthermore, the design design is carried out to become a machine. After the machine is finished, it is tested to find out whether the machine is able to work optimally to meet the company's target.